Predicting functional remission in patients with schizophrenia: a cross-sectional study of symptomatic remission, psychosocial remission, functioning, and clinical outcome - Valencia, Marcelo (Neuropsychiatr Dis Treat, 2015)
BACKGROUND: New approaches to assess outcome in schizophrenia include multidimensional measures such as remission, cognition, psychosocial functioning, and quality of life. Clinical and psychosocial measures have been recently introduced to assess functional outcome. OBJECTIVE: The study presented here was designed to examine the rates of symptomatic remission, psychosocial remission, global functioning, and clinical global impressions in a sample of schizophrenia outpatients in order to assess functional remission and to identify predictive factors for functional remission. METHODS: A total of 168 consecutive Mexican outpatients receiving pharmacological treatment at the National Institute of Psychiatry in Mexico City were enrolled in a cross-sectional study. Symptomatic remission was assessed according to the definition and criteria proposed by the Remission in Schizophrenia Working Group using the Positive and Negative Symptom Scale. Psychosocial remission was assessed according to Barak criteria using the Psychosocial Remission in Schizophrenia scale. Functioning was measured with the Global Assessment of Functioning, and clinical outcome with the Clinical Global Impressions (CGI) Scale. RESULTS: Findings showed that 45.2% of patients fulfilled the symptomatic remission criteria, 32.1% achieved psychosocial remission, and 53% reported adequate functioning. However, the combination of these three outcome criteria – symptomatic, psychosocial remission, and functioning – indicated that 14.9% of the patients achieved our predefined functional remission outcome. The logistic regression model included five predictive variables for functional remission: (1) being employed, (2) use of atypical antipsychotics, (3) lower number of medications, (4) lower negative symptom severity, and (5) lower excitement symptom severity. CONCLUSION: The study demonstrated that symptomatic remission, psychosocial remission, and functioning could be achievable goals for a considerable number of patients. The outcome of functional remission was achieved by a minority of patients, less than 15%. New approaches should include multidimensional measures to assess functional outcome in schizophrenia research.